Studi Pengaruh Kombinasi Pengelasan GMAW dan SMAW dengan Metode WAAM: Studi Pengaruh Kombinasi Pengelasan GMAW dan SMAW dengan Metode WAAM - Jatmoko; Hanifah, Anis; Pratama, Muhammad Aditya; Rohimsyah, Fikan Mubarok (SPECTA Journal of Technology, 2023)
The development of technology and science is multiplying, so it affects the industrial sector in Indonesia, namely the industry that manufactures machine elements, especially in the automotive sector, which commonly uses metal as raw material. The manufacturing sector's production in the automotive industry tends to increase annually. The need for metal as raw material is constantly increasing. The WAAM welding method be utilized as one of the innovations in the industrial world that potentially reduces the use of raw metal materials by replacing them with the results of the WAAM process. In this study, a combination of GMAW and SMAW welding using the WAAM method was carried out by adding material in layers and switching between the two types of welding. The welding process is carried out by varying the current (high, medium, and low). Then, a tensile test was carried out to determine the mechanical properties of the combination results. Based on the tensile test results, it is known that the high current variation gives the best results, the increasing current lead to an enhancement of the mechanical properties. Finally, using high currents will give the best result for application in the engineering and automotive sector.